(untitled) (Physical Education, Health and Social Sciences, 2025)
Advances in multidisciplinary imaging have revolutionized the early detection, management, and treatment planning of cancer. This review focuses on the fusion of imaging with cross- disciplinary technologies, such as radiomics and artificial intelligence (AI), that collectively help provide a full characterization of tumor properties. The combination of imaging with laboratory results, genomic findings, and clinical data may facilitate accurate staging and patient-centered treatment allocation. Therapeutic and screening programs guided by images have shown significant potential to reduce mortality and treatment toxicities. This review emphasizes the need for academia, biotechnology, and pharmaceutical industries to collaborate synergistically in order to continually introduce new developments in cancer imaging. Future progress in the interdisciplinary combination of imaging science and technological development will further geometrically enhance our diagnostic potential, therapeutic control efficacy, the oncological patient’s tolerance, and treatment outcomes for cancer disease processes, with AI-guided techniques increasingly becoming a core contributor to improved precision oncology, along with better overall patient care.